Health tourism and physical literacy: a qualitative exploration of elderly visitors’ experiences after rehabilitation at Slovenian health resorts - Kokot, Katja; Turnšek, Maja (Academica Turistica - Tourism and Innovation Journal, 2022)
The promotion of physical literacy is an opportunity to multiply significant health benefits in the ageing society. In Slovenia, health resorts are one of the most common prime areas for health enhancement that offer numerous services for individuals to improve their health and form an important pillar of the social tourism and healthcare sector. The aim of this research is to explore the role of medical rehabilitation at the Slovene health resorts in the processes of increasing the physical literacy of their patients. 21 semi-structured interviews were conducted with previous guests of Slovene health resorts that have undertaken medical rehabilitation. The analysis indicates that the most common approach is providing lectures about physical activity followed by group or individual physical regimes organised for the patients with similar health concerns. These actions target two dimensions of physical literacy: the competence and the knowledge/understanding dimension. However, the eventual omission of prescribed physical activity following the rehabilitation is an issue concerning the motivation dimension of physical literacy, which should thus be addressed more in the future. The findings contribute to understanding the role of medical rehabilitation at Slovene health resorts by applying the physical literacy model for older adults. The study provides valuable insights regarding the long-term benefits of rehabilitation at the health resorts on individuals' level of physical literacy. The results are helpful for both the tourism and medical sectors.